THE PAINTED FOX OF IVAN FRANKO AND THE PRINCIPLES OF QUANTUM MECHANICS (psychological and physical transformations of Mykit the Fox in the tale of Ivan Franko as an explanation of the trends of the functionality of the principles of quantum mechanics in t - Холод, О. (Київський національний університет імені Тараса Шевченка, 2022)
The article considers the tendencies of three principles of quantum mechanics for the micro world (uncertainty principle, additionality or complementarity principle and superposition or superposition principle) as having similarities with the tendencies of analysis of processes occurring in the macro world. The hypothesis is proved during the analysis of the fairy tale "Painted Fox" by Ivan Franko. The aim of the research was to identify, search for and describe the psychological and physical transformations of Fox Mykyta in Ivan Franko's fairy tale as an explication of the tendencies of the functionality of the principles of quantum mechanics in the macro world. Among the research methods were chosen methods of analysis, synthesis, content analysis on the units of "image" and "theme". We have chosen the following procedure as the research method: search for publications related to the problem analyzed by us; implementation of content analysis by unit "image" and "theme"; classification of identified fragments of the text of the fairy tale "Painted Fox" according to three criteria: "Compliance with the principle of uncertainty", "Compliance with the principle of complementarity" and "Compliance with the principle of superposition". Based on the analysis, it was concluded that the trends reflected in the three principles of quantum mechanics for studying the processes of the micro world (uncertainty, principle of additionality or complementarity and the principle of superposition or superposition) are clearly fixed in macro world processes.

Розглядаються тенденції трьох принципів квантової механіки для мікросвіту (принцип невизначеності, принцип додатковості, або доповнюваності та принцип суперпозиції, або накладання) як такі, що мають спільні риси з тенденціями аналізу процесів, що відбуваються в макросвіті. Гіпотеза доводиться під час аналізу казки "Фарбований Лис" Івана Франка. Метою дослідження стали ідентифікація, пошук й опис психологічних і фізичних трансформацій Лиса Микити в казці Івана Франка як експлікація тенденцій функціональності принципів квантової механіки в макросвіті. Серед методів дослідження були обрані методи аналізу, синтезу, контент-аналізу за одиницями "образ" і "тема". Методикою дослідження ми обрали таку процедуру: пошук публікацій, дотичних за проблематикою до аналізованої нами проблеми; здійснення контент-аналізу за одиницею "образ" і "тема"; класифікація ідентифікованих фрагментів тексту казки "Фарбований Лис" за трьома критеріями: "Відповідність принципу невизначеності", "Відповідність принципу доповнюваності" і "Відповідність принципу суперпозиції. На базі здійсненого аналізу було сформульовано висновок про те, що тенденції, відбиті у трьох принципах квантової механіки для вивчення процесів мікросвіту (принцип невизначеності, принцип додатковості, або доповнюваності та принцип суперпозиції, або накладання), яскраво фіксуються в процесах макросвіту.
ФАРБОВАНИЙ ЛИС ІВАНА ФРАНКА Й ПРИНЦИПИ КВАНТОВОЇ МЕХАНІКИ (психологічні й фізичні трансформації Лиса Микити в казці Івана Франка як експлікація тенденцій функціональності принципів квантової механіки в макросвіті)
Keywords: principles of quantum mechanics; Ivan Franko; Fox Mykyta; Painted Fox; uncertainty principle; additionality principle; superposition principle; принципи квантової механіки; Іван Франко; Лис Микита; Фарбований Лис; принцип невизначеності; принцип додатковості; принцип суперпозиції